Some initial experimental results on the conditions of free water layer formation in horizontal pipes - Nguyen Duy Thien; Nguyen Van Diep; Duong Ngoc Hai; Nguyen Hong Phan (Vietnam Journal of Mechanics)
This paper presents an experimental facility conducted in Hanoi Institute of Mechanics to investigate multiphase How pattern in the pipes. First and foremost, it is used to define the conditions of water layer formation in the horizontal pipe.